2016
DOI: 10.18203/2394-6040.ijcmph20151564
|View full text |Cite
|
Sign up to set email alerts
|

Occupational stress and its associated health disorders among bus drivers

Abstract: Background: Bus drivers as compared to workers in other jobs, are more likely to experience cardiovascular diseases, gastrointestinal disorders and musculoskeletal disorders. Occupational stress is believed to play a significant role in causing these problems. The objective of this study is to assess the occupational stress and to find the prevalence of cardiovascular, gastrointestinal and musculoskeletal disorders among bus drivers and its association if any, with occupational stress. Methods: Cross sectional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 4 publications
1
4
1
3
Order By: Relevance
“…Our results revealed that one third of participants had high blood pressure, which is higher than the national figure (26.8%) (8), and there was a significant association between workplace stress and high blood pressure, even after adjustment for other confounding factors. This finding was similar to others studies (11,16,31,32). The reason why there has been a high prevalence of high blood pressure in the current work may be related to higher percentages of lifestyle risk factors among study participants.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our results revealed that one third of participants had high blood pressure, which is higher than the national figure (26.8%) (8), and there was a significant association between workplace stress and high blood pressure, even after adjustment for other confounding factors. This finding was similar to others studies (11,16,31,32). The reason why there has been a high prevalence of high blood pressure in the current work may be related to higher percentages of lifestyle risk factors among study participants.…”
Section: Discussionsupporting
confidence: 93%
“…In this study over 80% of the bus drivers showed varying degrees of workplace stress. In comparison to other studies, lower rates of moderate to high stress were reported among city bus drivers in the Islamic Republic of Iran (74.5%), Mumbai, India (66.2%), and Colombia (40.5%) (15)(16)(17). Bus drivers who encountered stress problems in the present study were characterized by being older, having lower educational achievement, facing more social conflicts and having more experience in driving (> 10 years and PDAR ≥ 0.5).…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…In the current study, none of the occupational drivers reported that they had any disease or health problem in the previous 6 months, including any mental or psychological problems. Contrary to this, a study conducted among bus drivers in Mumbai, India, revealed that hypertension, musculoskeletal problems and gastrointestinal diseases were the results of occupational stress among the study population (30). The factors identified were primarily shift schedule, irregular timings of food intake, compromised nutrition, long hours of driving and traffic jams causing occupation-related stress (30).…”
Section: Discussionmentioning
confidence: 89%
“…Dále byl zjištěn signifikantní vztah mezi vnímanou pracovní kontrolou a katecholaminy v moči. Jiná studie provedená na 210 indických řidičích autobusu (Taklikar, 2016), kteří vyplňovali dotazník zdravotních obtíží v souvislosti se stresem, prokázala, že 24 % trpělo hypertenzí, 52 % dyspepsií a regurgitací a 79 % bolestí zad, přičemž míra nemocnosti se zvyšovala úměrně se zvyšující se mírou zaměstnaneckého stresu. Lze shrnout, že řidiči vykazují zvýšenou míru kardiovaskulárních, muskuloskeletárních a gastrointestinálních onemocnění (Kompier, 1996).…”
Section: Hlavní Stresory Profese a Jejich Důsledkyunclassified